Mechanical, Thermal and Surface Investigations of Chitosan/Agar/PVA Ternary Blended Films - Esam A. El-Hefian; Mohamed Mahmoud Nasef; Abdul Hamid Yahaya (E-Journal of Chemistry)
The mechanical and thermal properties of chitosan/agar/poly vinyl alcohol (CS/AG/PVA) ternary blended films having various proportions considering chitosan as the main component were investigated. The various variables static water contact angle such as contact angle, drop base area, drop volume and drop height was also studied in correlation with the variation of time. Results obtained from mechanical measurements showed a noticeable increase in the tensile strength (TS) coincided with a sharp decrease in elongation percent at break (E%) of blended films with increasing agar and PVA contents. The DSC results prevailed the development of an interaction between chitosan individual components: agar and PVA. Moreover, an enhancement of the wettability of the blends was obtained with increasing agar and PVA contents. It was also found that the pure CS film and the blended films with 90/05/05 and 80/10/10 compositions were more affected by time than blended films with other compositions when the contact angle, the drop height and the drop length were studied as a function of time. In addition, when the drop is initially placed on the substrate, the drop area and the drop volume of all films remained almost constant up to a certain time after which they showed a slight difference with the elapse of time.